Bispecific antibody (HER2 × mPEG) enhances anti-cancer effects by precise targeting and accumulation of mPEGylated liposomes. (15th July 2020) - Chen, I-Ju; Cheng, Yi-An; Ho, Kai-Wen; Lin, Wen-Wei; Cheng, Kai-Wen; Lu, Yun-Chi; Hsieh, Yuan-Chin; Huang, Chien-Chiao; Chuang, Chih-Hung; Chen, Fang-Ming; Su, Yu-Cheng; Roffler, Steve R.; et al.
Abstract: Targeted antibodies and methoxy-PEGylated nanocarriers have gradually become a mainstream of cancer therapy. To increase the anti-cancer effects of targeted antibodies combined with mPEGylated liposomes (mPEG-liposomes), we describe a bispecific antibody in which an anti-methoxy-polyethylene glycol scFv (αmPEG scFv) was fused to the C-terminus of an anti-HER2 (αHER2) antibody to generate a HER2 × mPEG BsAb that retained the original efficacy of a targeted antibody while actively attracting mPEG-liposomes to accumulate at tumor sites. HER2 ×mPEG BsAb can simultaneously bind to HER2-high expressing MCF7/HER2 tumor cells and mPEG molecules on mPEG-liposomal doxorubicin (Lipo-Dox). Pre-incubation of HER2 × mPEG BsAb with cells increased the endocytosis of Lipo-DiD and enhanced the cytotoxicity of Lipo-Dox to MCF7/HER2 tumor cells. Furthermore, pre-treatment of HER2 × mPEG BsAb enhanced the tumor accumulation and retention of Lipo-DiR 2.2-fold in HER2-high expressing MCF7/HER2 tumors as compared to HER2-low expressing MCF7/neo1 tumors. Importantly, HER2 × mPEG BsAb plus Lipo-Dox significantly suppressed tumor growth as compared to control BsAb plus Lipo-Dox in MCF7/HER2 tumor-bearing mice. These results indicate that HER2 × mPEG BsAb can enhance tumor accumulation of mPEG-liposomes to improve the therapeutic efficacy of combination treatment. Anti-mPEG scFv can be fused to any kind of targeted antibody to generate BsAbs to actively attract mPEG-drugs and improve anti-cancer efficacy. Statement of Significance: Antibody targeted therapy and PEGylated drugs have gradually become the mainstream of cancer therapy. To enhance the anti-cancer effects of targeted antibodies combined with PEGylated drugs is very important. To this aim, we fused an anti-PEG scFv to the C-terminal of HER2 targeted antibodies to generate a HER2×mPEG bispecific antibody (BsAb) to retain the original efficacy of targeted antibody whilst actively attract mPEG-liposomal drugs to accumulate at tumor sites. The present study demonstrates pre-treatment of HER2×mPEG BsAb can enhance tumor accumulation of mPEG-liposomal drugs to improve the therapeutic efficacy of combination treatment. Anti-mPEG scFv can be fused to any kind of targeted antibody to generate BsAbs to actively attract mPEG-drugs and improve anti-cancer efficacy. Graphical abstract: Image, graphical abstract